The Influence of Digital Marketing on Purchase Intention Mediated by Consumer Engagement and Moderated by Consumer Trust - Wulansari Wulansari; Hermanto Yaputra; Steven Tanjaya; Ailen Tania; Vebrina Anggraini Tambunan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This research aims to evaluate the impact of Digital Marketing on Consumer Purchase Intention at beauty clinics in Jakarta, with Consumer Engagement as a mediating variable and Consumer Trust as a moderating variable. The background of this study is the rapid growth of the beauty clinic industry in Jakarta, which is estimated to reach 672 units by 2024, yet the effectiveness of Digital Marketing in influencing purchase decisions remains in question. For the research method, a quantitative approach was used with Structural Equation Modeling (SEM) techniques through AMOS and SPSS 22 software. Data were collected from 330 respondents who are active on social media and have used services from three major beauty clinics in Jakarta: Erha Clinic, Derma Express Clinic, and Impressions Body Care Centre. The findings show that Digital Marketing has a positive and significant influence on Purchase Intention. Consumer Engagement has been shown to significantly mediate the relationship between Digital Marketing and Purchase Intention. Additionally, Consumer Trust has been shown to significantly moderate the relationship between Digital Marketing and Consumer Engagement. These results emphasize that to enhance the effectiveness of Digital Marketing, consumer involvement and trust in the brand are very important factors in supporting purchasing decisions.